Morphological-molecular characterization and phylogenetic relationships of a new Trichuris species (Nematoda: Trichuridae) parasitic on Holochilus chacarius (Cricetidae: Sigmodontinae) from the Chaco ecoregion (Argentina) - Robles, Maria del Rosario (2018)
A new Trichuris species isolated from Holochilus chacarius (Cricetidae: Sigmodontinae) from the Chaco ecoregion in Argentina is described based on morphological characteristics and mitochondrial (cox1, cob) and nuclear (ITS2) markers. The new species is distinguished from 27 species of Trichuris from North and South American rodents based on morphological and biometrical features, such as the absence of a spicular tube, presence of a cylindrical spicular sheath, non-protrusive vulva, length of spicule, and proximal and distal cloacal tube. In addition, the results based on three molecular markers of the new species and three Trichuris species previously analysed from sigmodontine rodents: Trichuris pardinasi, Trichuris navonae and Trichuris bainae confirmed that the specimens here studied belong to a different species. Molecular data are further used to discuss the phylogenetic relationships among the Trichuris species of rodents from Argentina. The combined analysis of mitochondrial genes (cox1 and cob) revealed four clades corresponding with four different species of Trichuris. T. navonae (Akodontini rodents) and T. massoiai n. sp. as a sister group related to T. bainae (Oryzomyini rodents) and separated of T. pardinasi (Phyllotini rodents).